2022
DOI: 10.3390/bs12100381
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Molecular Assessment of Self-Processes in Neurotypical Subjects Using a Single Cognitive Behavioral Intervention Evoking Autobiographical Memory

Abstract: In the last 20 years, several contributions have been published on what concerns the conceptual and empirical connections between self-processes. However, only a limited number of publications addressed the viability of those processes to characterize mental health in neurotypical subjects with a normative pattern of neurodevelopment. Furthermore, even fewer experiments focused explicitly on the complexity of studying neurotypical phenomenal data. On the one hand, this normative pattern is commonly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…This subsequent paper will plot and illustrate the total protein profiles of the 92 subjects as an innovative probe using saliva. Subsequently, the authors show that the 92 young adults showed specific expected protein profiles present in saliva, which correspond to the four psychologically different subgroups (self-awareness, self-consciousness, reflective self, and pre-reflective self) found in the neurotypical subjects with discrete self-processes [56].…”
Section: Modelingvis: Limitations and Future Scopementioning
confidence: 96%
See 1 more Smart Citation
“…This subsequent paper will plot and illustrate the total protein profiles of the 92 subjects as an innovative probe using saliva. Subsequently, the authors show that the 92 young adults showed specific expected protein profiles present in saliva, which correspond to the four psychologically different subgroups (self-awareness, self-consciousness, reflective self, and pre-reflective self) found in the neurotypical subjects with discrete self-processes [56].…”
Section: Modelingvis: Limitations and Future Scopementioning
confidence: 96%
“…The outcome of this study is thus to correlate the four different mental health strata [17,56] with the four different molecular profiles using MODeLING.Vis as a GUI toolbox. The practical proposition of this analysis is to accomplish the molecular assessment of self-regulation processes with separate cognitive and molecular characteristics.…”
Section: Modelingvis: Limitations and Future Scopementioning
confidence: 99%